Aktivitas Antibakteri Ekstrak Etanol Daun Daruju (Acanthus ilicifolius Linn) terhadap Escherichia coli - Annisa Firdaus, Navisa; Widiyantoro, Ari; Mardhia, Mardhia (Journal of Comprehensive Science, 2025)
Escherichia coli can be pathogenic and will cause several diseases including diarrhea, urinary tract infections, meningitis in newborns and wound infections, especially in wounds in the abdomen. The daruju plant (Acanthus ilicifolius Linn.) is often used by the community, especially West Kalimantan, for energy recovery after childbirth, rheumatism medicine, abdominal pain medicine, hypertension, flatulence, ulcers and antidotes for snake venom. In previous studies, it was also found that daruju leaves (Acanthus ilicifolius Linn.) have antibacterial activity. The purpose of this study is to determine the antibacterial activity of Daruju leaf ethanol extract (Acanthus ilicifolius Linn.) in West Kalimantan against Escherchia coli. Phytochemical screening of ethanol extract from daruju leaves (Acanthus ilicifolius Linn.) was carried out by a qualitative method using several reagents. Test extracts were made in concentrations of 20 mg/mL, 30 mg/mL, 40 mg/mL, 50 mg/ml, and 60 mg/mL with ethanol as a solvent. The antibacterial activity test was carried out by the disc diffusion method and measured the bacterial growth inhibition zone. The results of this study stated that the ethanol extract of daruju leaves (Acanthus ilicifolius Linn.) contains secondary metabolites, namely alkaloids, flavonoids, phenols, steroids, and terpenoids. There were no inhibitory zones on the growth of Escherichia coli at all concentrations of the tested extracts. In conclusion, ethanol extract of daruju leaves (Acanthus ilicifolius Linn.) had no antibacterial activity against Escherichia coli at all concentrations of the tested extracts.